CO2 snow jet cleaning as a roll-to-roll compatible method for deburring IMI substrates after laser patterning. (1st March 2023) - Wagner, M; Distler, A; Schmidt, H-DHD; Classen, A; Stubhan, T; Koegl, M; Illg, J; Brabec, C J; Egelhaaf, H-JHJ
Abstract: Burring is commonly encountered upon patterning of dielectric-metal-dielectric (DMD) transparent electrodes by laser ablation. These burrs are conductive and thus lead to shunting of the (opto-)electronic devices built upon these electrodes. In this work, CO2 snow jet blasting is presented as a convenient and reliable method for deburring laser-patterned DMD electrodes during roll-to-roll manufacturing of organic solar modules. As CO2 snow jet blasting significantly reduces the extent of shunting and concomitantly avoids scratching the electrode, the photoelectrical conversion efficiencies of the solar modules thus produced are higher than those obtained for traditional deburring techniques.